OPTIMALISASI LITERASI SISWA KELAS II MELALUI BIMBEL MEMBACA MIN 2 KOTA PALANGKA RAYA - Napisah, Nur; Istiyati Mahmudah (Universitas Nias Raya, 2024)
This research aims to optimize the literacy of second-grade students through a reading tutoring program at MIN 2 Kota Palangka Raya. The program was conducted from August to early October, involving five students as research subjects. The method used is a qualitative approach with techniques such as observation, interviews, and documentation to collect data. In this guidance, students are provided with reading materials and techniques tailored to individual needs, including a personal approach that helps students understand the content of the reading. The research results show a significant improvement in students' reading abilities, including reading speed, comprehension of the text, and their interest in literacy activities. This program has proven effective in enhancing students' literacy through a structured guidance approach that focuses on the characteristics of the students. The recommendation from this research is further development of the reading guidance program to reach more students and support literacy achievement on a broader scale.